NILAI DALAM BUDAYA LARUNG SESAJI GUNUNG KELUD - Fatimah, Raihana; Arum, Putri Dewi Andan; Ratnasari, Tri Ayu; Dewi, Sintia (Studi Budaya Nusantara, 2019)
Abstract The purpose of this study is to examine the cultural values of Pancasila in the Mount Kelud offerings asa hope to create a Gemah Ripah Loh Jinawi The background of this study stems from cultural differencesand beliefs in Indonesia. This diversity serves to maintain the basis of community identity. One of them isin agriculture, which is Larung Sesaji Gunung Kelud which contains Pancasila values. This research wasconducted in September-November 2019 in the Sugihwaras Village Area, Ngancar District, KediriRegency, East Java. Using qualitative research with techniques to conduct interviews, observation,documentation, and studio studies. Based on the research results Larung Sesaji activities, this studyreflects the values of the Pancasila precepts. According to the community's trust these activities arebased on gratitude for agricultural products in Kediri Regency with the hope of becoming a weak region ofGemah Ripah Loh Jinawi.